The Authority Of The Connextity Court In Corruption Cases to Realize Legal Certainty - Soeseno, Ambar; Wibobo, Basuki Resko; Teepapal, Tanawat (Journal Evidence Of Law, 2024)
: This research discusses the authority of the connexity court in handling corruption cases involving military personnel as an effort to realize legal certainty in Indonesia. Data from the Corruption Eradication Commission shows that corruption in Indonesia, including those involving the military, often faces law enforcement obstacles due to overlapping jurisdictions between the Corruption Eradication Commission and military institutions. This research highlights the urgency of reform in the authority of the connexity court to overcome legal uncertainty caused by jurisdictional dualism. Based on an analysis of the theory of legal certainty, the theory of authority, and the theory of connexity, it is found that the current regulations have not been able to provide the Corruption Eradication Commission with full authority in the investigation and prosecution of connexity corruption cases. This study identifies a significant research gap, namely the lack of studies that specifically discuss connexity trials in the context of corruption involving the military. Therefore, this research aims to analyses the current regulation and implementation of the authority of the connexity court, as well as provide policy recommendations to improve existing regulations. Thus, the results of this study are expected to contribute to legal reform in Indonesia, especially in eradicating corruption that is more effective and consistent, and realizing better legal certainty.